HIGHER EDUCATION IN FRANCE: HISTORICAL DEVELOPMENT - Durdas, Alla (The Modern Higher Education Review, 2019)
The article deals with the peculiarities of historical development and modern state of higher education in France. The periods of higher education development of France are determined and the complex and multi-level system of French higher education is considered. The importance of education for the strategy of national development of the country and civilization is emphasized. The importance of the study of the historical development of the university education in France has been substantiated. The stages of education development at the universities of France are outlined and features are considered. each of these stages. The types of higher education institutions in France and their peculiarities in the context of development tendencies are investigated. The present stage of the development of the system of French university education and the peculiarities of structural transformations is considered. The article describes the duality between the French higher education institutions and research centers, as well as the duality between educational institutions and educational programs. The peculiarities of functioning of universities, “big schools" and private institutions of higher education are studied. There is a strong centralized presence and the role of the state in the education of France, in particular in the organization of the educational process and in the financing of education, as well as in defining the fundamental principles of the educational process. The article focuses on the achievements of the French system of higher education and its uniqueness. The role and place of large schools in the system of higher education in France are highlighted. The leading elite schools and universities are mentioned, as well as the conditions for joining them. Attention was paid to the almost equal quality of education in the capital and in the province. Attention is drawn to the national character of the French higher education.